The Role of Islamic Education Curriculum Management in Enhancing Health Literacy Among Muslim Adolescents at MA Darussalam Krempyang - Niken Ristianah (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2025)
The study titled "The Role of Islamic Education Curriculum Management in Enhancing Health Literacy Among Muslim Adolescents at MA Darussalam Krempyang" addresses the ongoing challenge of low health literacy among Indonesian adolescents, despite the potential of Islamic education to effectively integrate health principles. MA Darussalam Krempyang serves as a distinctive example where the Islamic educational curriculum actively incorporates health education to address this gap. Through a qualitative case study approach, the research employs in-depth interviews with teachers, students, and school administrators, alongside curriculum analysis and literacy assessments, to explore how curriculum management influences health literacy outcomes. Key findings demonstrate that embedding health-related topics within Islamic jurisprudence (fiqh), theology (aqidah), and science subjects substantially enhances adolescents’ understanding of critical health issues including nutrition, hygiene, and reproductive health. This integration not only enriches students’ knowledge but also aligns health education with their religious and cultural contexts, making the learning both meaningful and relevant. The study concludes that effective curriculum management is crucial in bridging Islamic values with health education goals. Success depends on strategic alignment across educational objectives, curricular content, and evaluation mechanisms to ensure health literacy improvements are tangible and sustained. By emphasizing this synergy, MA Darussalam Krempyang exemplifies how madrasah aliyah settings can foster holistic adolescent development encompassing spiritual and physical well-being.